Investigating negative capacitance shunt circuit for broadband vibration damping and utilizing ACO for optimization - Wahid, Azni Nabela; Asan Gani, Abdul Muthalif; A. M. Nor, Khairul (International Association of Research and Science (IARAS), 2016)
This paper presents optimization of vibration damping for a rectangular thin plate using a single piezoelectric (PZT) patch shunted with negative capacitance, by utilizing the ant colony optimization (ACO) algorithm. The frequency range to be controlled is presented in the context of statistical energy analysis (SEA) where modal overlap factor (MOF) is considered i.e. MOF<1 (low), 1<MOF<2 (mid) and MOF>2 (high). The effects of two different shunt circuits on the system are studied; series and parallel resistor-negative capacitor (R-C). The governing equation of motion for a PZT patch shunt attached on a thin plate is obtained using Lagrange’s equation, and ACO algorithm is utilized to obtain the optimum spatial coordinate of the PZT patch and resistor values of the shunt circuit for the different frequency regions, targeting for maximum energy reduction of the vibrating thin plate.